2012
DOI: 10.1007/s11434-011-4907-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of sea-salt aerosols studied by high-speed photography

Abstract: Morphological changes with decreasing relative humidity (RH) of supersaturated sea-salt aerosol droplets on a quartz substrate were observed using a high-speed video-camera. Stable gypsum (CaSO 4 ·2H 2 O) or the metastable hemihydrate (CaSO 4 ·0.5H 2 O) were precipitated as the RH decreased. The dynamic process of crystal growth under steady-state humidity was studied by controlling the RH; the metastable hemihydrate was precipitated at 70.5%-77.1% RH, and the apparent crystal growth rate was between 1. 42 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…These bassanite nucleation studies highlight the key role of hydration effects during the crystallization of calcium sulfate phases, which are likely to change substantially as the activity of water is significantly reduced at high salt/low water contents. Another observation pointing in the same direction is the formation of bassanite during the evaporation of droplets of CaSO 4 solutions at room temperature 15,16 . The relative humidity (RH < 80%) and the time-dependent availability of water appear to be the controlling factors for phase selection in this system.…”
Section: Introductionmentioning
confidence: 80%
“…These bassanite nucleation studies highlight the key role of hydration effects during the crystallization of calcium sulfate phases, which are likely to change substantially as the activity of water is significantly reduced at high salt/low water contents. Another observation pointing in the same direction is the formation of bassanite during the evaporation of droplets of CaSO 4 solutions at room temperature 15,16 . The relative humidity (RH < 80%) and the time-dependent availability of water appear to be the controlling factors for phase selection in this system.…”
Section: Introductionmentioning
confidence: 80%
“…Also, bassanite can form spontaneously when droplets of CaSO 4 solutions are rapidly evaporated (i.e. when the level available hydration water is rapidly decreased) at ambient conditions (Qian et al, 2012;Shahidzadeh et al, 2015). Experiments at 60 °C were monitored over periods of up to two years of reaction, but the precipitate remained phase-pure gypsum (according to PXRD, with its detection limit of around 1%) in all studied cases (Ossorio et al, 2014).…”
Section: ±mentioning
confidence: 99%
“…This highlights the fact that while speculative, differences in droplet size, shape, substrates, as well as the other factors discussed above could all potentially be contributing factors while comparing the transition temperatures between the methods presented here. The rate of dehydration has also been shown to be a major factor affecting the morphology of efflorescing particles in previous studies on seawater , as well as studies on pharmaceutical compounds , and could be the biggest cause of the different crystal structures at the same temperature seen here and needs to be investigated further.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies have also reported a different efflorescence crystal structure in seawater depending on the rate of decrease of RH due to different number of water molecules trapped in the dried particle. 62,63 Here, we investigate a range of model aerosol systems in the range −20 to +25 °C that covers a significant portion of tropospheric temperature (−60 to +25 °C) for O/C ratios between 0.38 and 0.67, which are below the critical O/C < 0.92 for LLPS. We varied the organic to inorganic ratio (OIR) of the systems to estimate the effect of the organic and inorganic components on the LLPS morphology temperaturedependence.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation